PENDAMPINGAN PENGEMBANGAN PRODUK ILMIAH PENDIDIKAN BAGI GURU DI YAYASAN NURUL HIDAYAH, BOJONGSARI, DEPOK - Anggara, Dameis Surya; Abdillah, Candra; Permana, Putut Said; Prasetyawan, Enggar (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
Effective learning can be achieved if the teacher is able to analyze the learning problem and solve it. One of the solutions to this problem is through research based on the creation of educational products. Based on the situation analysis, it was found that the teachers at Nurul Hidayah Foundation had not been maximized in conducting research that produced educational products as solutions to learning problems. This difficulty is felt because teachers still do not understand how to conduct research that produces educational products. This situation has an impact on the ineffectiveness of learning undertaken. Based on that, community service is carried out with the aim of providing socialization and mentoring to teachers in developing educational scientific products with elementary and junior high school teachers in the Nurul Hidayah Foundation. The activity was carried out using lecture, discussion and workshop methods. The results obtained are the teacher is able to understand and implement how to register problems, identify problems, determine problems, and determine the topic of research based on educational products.